Secret files of the Inquisition. Episode II, The tears of Spain - Rabinovitch, John David; King, Colin (Television director); Feore, Colm, 1958-; Inquisition Productions, Inc.; Soundview Media Partners ([Canada?] : Inquisition Productions, Inc., 2006)
Fernando and Isabel proclaim themselves the Catholic Monarchs. In the war to drive the remaining Muslims from the south of the Kingdom their scapegoats become the Conversos, Jews who have converted to Christianity and who are now accused of being traitors and heretics secretly trying to undermine the Church. The Spanish Inquisition is born and a campaign of terror begins.
Originally broadcast on television in 2006.
Narrator: Colm Feore.
Director of photography, Pieter Stathis ; editor, Paul Tourneur ; music, John Sereda & Mike Thomas.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 20, 2019)
Keywords: Catholic Church -- History; Inquisition; Inquisition -- Spain; Documentary television programs; Historical television programs; Historical reenactments (Television programs); Television mini-series.; Nonfiction television programs; Internet videos; Streaming video